Factors Influencing the Optimization of Asset Management and Reporting at the Regional Financial and Asset Management Agency of Mahakam Ulu Regency - Sophia Hipui; Fibria Indriati Dwi Liestiawati (Dinasti Research, 2025)
This study aims to analyze the factors that influence the management and reporting of regional assets at the Regional Finance and Asset Management Agency (BPKAD) of Mahakam Ulu Regency, and to formulate strategies to optimize asset management and reporting in the region. The approach used in this study is post-positivism, which allows researchers to view asset management not only technically, but also in the social, political, and ideological contexts that influence public policy. Using qualitative methods, this study explores the perceptions and experiences of stakeholders involved in asset management, through in-depth interviews with key informants, including the Head of BPKAD and other related parties. The results of the study indicate that there are several factors that influence the effectiveness of asset management and reporting, including limited human resources, technological infrastructure problems, lack of coordination between SKPDs, and support from regional leaders. This study also formulates several strategies to overcome these obstacles, namely increasing human resource capacity through ongoing training, improving technological infrastructure, especially to improve internet access in remote areas, strengthening regulations and monitoring, and increasing coordination between SKPDs. With these strategies, it is hoped that asset management and reporting in Mahakam Ulu Regency can run more effectively, transparently, and accountably. This research provides an important contribution to regional asset management policy and can be a reference for further research in the field of regional governance.